PENGARUH PENGEMBANGAN KARIR, STRES KERJA DAN KESEHATAN KESELAMATAN KERJA (K3) TERHADAP KINERJA KARYAWAN PT. MUSI BANYUASIN INDAH-POM SEI SELABU (WILMAR PLANTATION) (Universitas Muhammadiyah Palembang, 2022)
The purpose of this study was to determine the effect of career development, work stress, and occupational health and safety (K3) on the performance of employees of PT. Musi Banyuasin Indah-POM Sei Selabu (Wilmar Plantation). In this study, a sample of 53 employees was taken. The sample method used is a random sampling method. This type of research is an associative research type. The data used in this study is primary data. The data collection technique used is a questionnaire. The quantitative method uses multiple linear regression analysis..The results of hypothesis testing show F_count (175.555) > F_table (2.40) then H_o is rejected and H_a is accepted. This indicates that there is an effect of career development, work stress and occupational health and safety (K3) on the performance of PT. Musi Banyuasin Indah-POM Sei Selabu (Wilmar Plantation). And t_(count ) X_1 (0,508), X_2 (3,034) and X_3 (2,511) > t_table (1,673) then for work stress and K3 H_0 is rejected and H_a is accepted, meaning that there is a significant effect of work stress and occupational health and safety (K3) on employee performance of PT. Musi Banyuasin Indah-POM Sei Selabu (Wilmar Plantation). Career development H_0 is accepted and H_a is rejected, meaning that there is no significant effect of career development on the performance of PT. Musi Banyuasin Indah-POM Sei Selabu (Wilmar Plantation).